2021
DOI: 10.3390/app112411672
|View full text |Cite
|
Sign up to set email alerts
|

Operando XAS of a Bifunctional Gas Diffusion Electrode for Zn-Air Batteries under Realistic Application Conditions

Abstract: In this study, operando X-ray absorption spectroscopy (XAS) measurements were carried out on a newly developed O2 bi-functional gas diffusion electrode (GDE) for rechargeable Zn-air batteries, consisting of a mixture of α-MnO2 and carbon black. The architecture and composition of the GDE, as well as the electrochemical cell, were designed to achieve optimum edge-jumps and signal-to-noise ratio in the absorption spectra for the Mn K-edge at current densities that are relevant for practical conditions. Herein, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This investigation will be undertaken through in situ extended X‐ray absorption fine structure (EXAFS), with the approach described in ref. [60] Nevertheless, the observed modification proves that cathodic and cathodic/anodic polarization in Zn 2+ ‐containing electrolytes brings about evident and progressive structural modifications. Moreover, the observed changes in vibrational structure clearly correlate with the modification of the voltammetric response pinpointed in Figure 4 and the microscopic morphological changes highlighted in Figure 5.…”
Section: Resultsmentioning
confidence: 90%
“…This investigation will be undertaken through in situ extended X‐ray absorption fine structure (EXAFS), with the approach described in ref. [60] Nevertheless, the observed modification proves that cathodic and cathodic/anodic polarization in Zn 2+ ‐containing electrolytes brings about evident and progressive structural modifications. Moreover, the observed changes in vibrational structure clearly correlate with the modification of the voltammetric response pinpointed in Figure 4 and the microscopic morphological changes highlighted in Figure 5.…”
Section: Resultsmentioning
confidence: 90%
“…Previous reports also demonstrated that the stabilized valence of Mn by introducing Ni atoms in Mn oxide structure is due to interaction between Ni and Mn atoms, which can prevent the formation of the less active Mn 3 O 4 during ORR/OER [57] . Furthermore, a significant increase in FT of M−O signal intensity of Ni 0.2 Mn 0.8 Co 2 O 4 relative to MnCo 2 O 4 is noticed, which may be attributed to the formation of additional bonds in the defective manganese oxide lattice [58] . Interestingly, at fully charged and discharged states, both catalysts reveal a rise in their FT signal intensity.…”
Section: Resultsmentioning
confidence: 99%
“…[57] Furthermore, a significant increase in FT of MÀ O signal intensity of Ni 0.2 Mn 0.8 Co 2 O 4 relative to MnCo 2 O 4 is noticed, which may be attributed to the formation of additional bonds in the defective manganese oxide lattice. [58] Interestingly, at fully charged and discharged states, both catalysts reveal a rise in their FT signal intensity. Apparently, the FT peak intensity of MnÀ O bond for Ni 0.2 Mn 0.8 Co 2 O 4 possesses a higher signal intensity than that of MnCo 2 O.…”
Section: Electrochemical Catalytic and Rechargeable Zinc-air Battery ...mentioning
confidence: 98%
“…Additionally, XAS is a commonly used technique to examine atomic local structure as well as electronic states. Usually, an X-ray strikes an atom and excites a core electron that can either be promoted to an unoccupied level or ejected from the atom [ 73 ]. It can interpret the properties of catalytic materials in situ and operand.…”
Section: Synthesis Methods For (Fe-co-ni-zn)-based Mofsmentioning
confidence: 99%